Development of an immunochromatographic lateral flow strip test for the rapid detection of diclofenac in medicinal wine. Issue 1 (1st January 2020) - Yang, Xingdong; Wang, Yinbiao; Yang, Jifei; Sun, Zhongke; Chu, Cuiwei; Yue, Zonghao; Li, Lili; Hu, Xiaofei
ABSTRACT: A rapid immunochromatographic lateral flow strip test (ILFST) of competitive format for the detection of diclofenac (DCF) in medicinal wine samples was developed. The half-inhibitory concentration (IC50 ) values of the ILFST for DCF and the limit of detection (LOD) in DCF-spiked samples were 0.66 and 0.15 ng/mL, respectively. Recoveries of DCF from spiked medicinal wine samples were from 84.4% to 85.9% within an assay (intra-assay) and from 83.7% to 88.4% between assays (inter-assay). The coefficients of variation (CV) for intra-assay and inter-assay were 4.10–7.56% and 4.71–8.94%, respectively. These results indicated that the ILFST was highly sensitive and re-producible. The same authentic medicinal wine samples were tested by both ILFST and high-performance liquid chromatography (HPLC) respectively. The results showed no significant differences between the two methods. Therefore, the ILFST can be widely used as a convenient tool for both qualitative and quantitative detection of DCF residues in medicinal wine samples.